Immunization with the pan-fungal vaccine, NXT-2a, reduces fungal burden following serial intravaginal challenges with C. albicans in a non-human primate model of experimental vulvovaginal candidiasis - Daniel A. Wychrij; Whitney Rabacal; Taylor I. Chapman; Hubertine M.E. Willems; Casey Ellen Pac; Kwadwo O. Oworae; Karen A. Norris (PLoS ONE, 2026)
Worldwide, recurrent vulvovaginal candidiasis (RVVC) is estimated to affect approximately 138 million women annually. Current treatments for RVVC include azole therapies; however, these frequently fail to prevent recurrence and are limited by potential teratogenic effects and increasing azole resistance. Despite these limitations, there are no approved fungal vaccines. While rodent models have advanced our understanding of disease pathogenesis and vaccine development, their variable susceptibility to human pathogens and limited ability to recapitulate human immune responses restrict translational progress. Here, we established a nonhuman primate model of VVC reinfection in Japanese macaques ( Macaca fuscata ) and used this model to evaluate the immunogenicity and protective efficacy of the ‘pan-fungal’ vaccine candidate NXT-2. We show that like humans, Japanese macaques are susceptible to VVC infections with C. albicans and display evidence of active infection through the formation of hyphae and recruitment of polymorphonuclear cells within the vaginal lumen. Infection and reinfection induced limited anti- Candida IgG responses and did not prevent reinfection. Notably, immunization of C. albicans reinfected macaques with NXT-2 induced robust systemic and mucosal anti-NXT-2 IgG antibody titers and reduced fungal burden in the vaginal lumen following subsequent rechallenge. Together, these data establish a valuable preclinical model for investigating host responses to VVC reinfection and for vaccine development, highlighting the potential of NXT-2 as a vaccine candidate to prevent RVVC.